(untitled) (Global Journal of Human-Social Science, 2024)
The quality of a school hinges not only on its curriculum and resources but also on the leadership that guides it Leadership in education stands for vision-setting collaboration development and more with the primary purpose of increasing the overall effectiveness of a school district Efficient managers can develop suitable teacher employment encourage students and ensure ideal conditions among learners Currently the education system in China is undergoing considerable alteration Lee 2019 The government focuses on innovation critical thinking and character development training Nevertheless converting these goals into measurable and achieved implementation is a hurdle to overcome The essay deliberates on a crucial connection between leadership in education and improving educational institutions in China The idea of success with all its diversity is also an intricate one changeable in sight and definition depending on who the stakeholders are and their priorities This study will go beyond the leadership styles of the effectiveness dimension and recognize different contexts and obstructions being faced in schools in China